High-performance uranium nitride composite fuel and preparation method thereof

By adding metal reinforced phases to the uranium nitride fuel and performing high-temperature sintering and surface micro-oxidation treatment, the problems of insufficient water oxidation resistance and reduced uranium density in the prior art are solved, and efficient and economical preparation of uranium nitride composite fuel is achieved.

CN120148914APending Publication Date: 2025-06-13MATERIAL INST OF CHINA ACADEMY OF ENG PHYSICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510327279.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The addition of the second phase in the prior art to improve the water oxidation resistance of uranium nitride fuel has limited effect, and the large addition of the second phase will reduce the uranium density in the composite fuel, affecting the economics of the fuel.

Method used

Add metal reinforced phase powders to uranium nitride, such as chromium, titanium, niobium, zirconium, tantalum, thorium, uranium, etc., and form a dense composite fuel through pressurization, high-temperature atmosphere sintering or field-assisted pressurization rapid sintering, and finally perform surface micro-oxidation treatment to form an oxide layer with excellent oxidation resistance.

Benefits of technology

It improves the water oxidation resistance of uranium nitride fuel, enhances the density of the fuel, reduces the sintering temperature, improves the economy and safety of the fuel, and realizes low-cost batch preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120148914A_ABST
    Figure CN120148914A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance uranium nitride composite fuel and a preparation method thereof. The preparation method comprises the following steps: uniformly mixing uranium nitride powder and metal reinforced phase powder, pressing, sintering in a high-temperature atmosphere or directly performing field-assisted pressurized rapid sintering, and finally performing surface micro-oxidation treatment to obtain the high-performance uranium nitride composite fuel. A metal reinforcement phase is added into uranium nitride, then pressing and high-temperature atmosphere sintering are performed or field-assisted pressurized rapid sintering is directly performed, and finally a uranium nitride / metal reinforcement phase composite fuel blank is subjected to surface micro-oxidation treatment, so that a uranium-nitrogen-oxygen ternary compound with excellent oxidation resistance and a metal oxide layer can be formed on the surface of the blank. The water oxidation resistance of the uranium nitride fuel is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of uranium fuels, and particularly to a high-performance uranium nitride composite fuel and a preparation method thereof. Background Art

[0002] Compared with uranium dioxide fuel, uranium nitride has a higher uranium atom density and higher thermal conductivity. When the uranium atom density of uranium nitride is higher, it can generate a higher power output in a nuclear reactor, or reduce the core size of the reactor while maintaining the same power level. When the thermal conductivity of uranium nitride is higher, during the operation of the nuclear reactor, the fuel rod can more effectively conduct the heat generated by the nuclear reaction, thereby reducing the fuel center temperature, reducing the risk of fuel damage due to overheating, and improving the safety and stability of the nuclear fuel in the reactor. At the same time, uranium nitride has good tolerance to high temperature and irradiation environments. Therefore, uranium nitride is considered a widely used fuel.

[0003] However, uranium nitride has poor resistance to water oxidation. This is because uranium nitride has high activity, and at room temperature, its oxidation resistance is poor and it is easy to react with oxygen in the air. When in a water environment, oxidation behavior will also occur to varying degrees. Below 300°C, uranium nitride reacts slowly with water; at higher temperatures above 300°C, its reaction with water will intensify, which may lead to a sharp decline in material properties and structural damage.

[0004] In order to improve the water oxidation resistance of uranium nitride, currently, mainly second phases with good antioxidant properties such as UO 2 , Cr, Si, Ti, etc. are added to uranium nitride to prepare high-performance uranium nitride composite fuel. The above method has limited improvement in the water oxidation resistance of uranium nitride fuel, and a large amount of addition of the second phase will also reduce the uranium density in the composite fuel, thereby reducing fuel economy and being unfavorable for the commercial application of uranium nitride fuel.

[0005] For example, Chinese Patent No. CN117854755A discloses a preparation method of a uranium-nitrogen-rhenium composite fuel pellet, which includes the following steps: S1: preparing a mixed powder of metallic uranium powder and metallic rhenium powder; S2: preparing a UNRe mixed powder using the mixed powder obtained in step S1; S3: pressing the UNRe mixed powder obtained in step S2 to obtain a composite fuel green body; S4: reacting the composite fuel green body obtained in step S3 with a mixed gas of nitrogen and ammonia at a predetermined temperature and a predetermined vacuum for a predetermined time to obtain a high-density composite fuel pellet. First, the water oxidation resistance of metallic uranium powder is much worse than that of uranium nitride. Second, by mixing uranium and rhenium, the improvement of water oxidation resistance is very limited. Summary of the Invention

[0006] In view of the problem in the prior art that adding a second phase has limited improvement on the water oxidation resistance of uranium nitride fuel, the present invention provides a high-performance uranium nitride composite fuel and a preparation method thereof.

[0007] The technical method of the present invention is as follows:

[0008] A preparation method of a high-performance uranium nitride composite fuel, comprising:

[0009] Mix uranium nitride powder and metal reinforcement phase powder evenly to obtain uranium nitride / metal reinforcement phase mixed powder;

[0010] Press the uranium nitride / metal reinforcement phase mixed powder into shape to obtain a green body of uranium nitride / metal reinforcement phase composite fuel;

[0011] Under a protective atmosphere, subject the green body of uranium nitride / metal reinforcement phase composite fuel to high-temperature atmosphere sintering to obtain a sintered body of uranium nitride / metal reinforcement phase composite fuel;

[0012] Perform surface micro-oxidation treatment on the sintered body of uranium nitride / metal reinforcement phase composite fuel to obtain a high-performance uranium nitride composite fuel.

[0013] The metal reinforcement phase powder of the present invention includes one or more of chromium, titanium, niobium, zirconium, tantalum, thorium, and uranium. Here, the average particle size of the metal reinforcement phase powder is 5 nm to 200 μm; the average particle size of uranium nitride is 500 nm to 800 μm. 10 vol.% to 50 vol.% of metal reinforcement phase powder is added to uranium nitride.

[0014] In the above steps, the steps of the surface micro-oxidation treatment include: under an air atmosphere or an argon-oxygen mixed gas atmosphere, perform surface micro-oxidation treatment on the sintered body of uranium nitride / metal reinforcement phase composite fuel at 50 to 150 °C for 2 to 24 h. Here, the density of the sintered body of uranium nitride / metal reinforcement phase composite fuel is 92% to 96%.

[0015] In the above steps, the steps of the high-temperature atmosphere sintering include: under a protective atmosphere, keep the green body of uranium nitride / metal reinforcement phase composite fuel at a temperature of 1000 to 2100 °C for 0.5 to 10 h; wherein, the protective atmosphere includes one or more of argon atmosphere, nitrogen atmosphere, argon atmosphere, and vacuum atmosphere. Here, the density of the green body of uranium nitride / metal reinforcement phase composite fuel is 45% to 60%.

[0016] The present invention also provides a high-performance uranium nitride composite fuel, which is obtained by the preparation method of the high-performance uranium nitride composite fuel described above. The thermal conductivity of the high-performance uranium nitride composite fuel at room temperature reaches 13.7 to 29.3 W·m -1 ·K -1, the coefficient of thermal expansion from room temperature to 100 °C is 7.6 to 10.5×10 -6 K -1 .

[0017] The present invention also provides a method for preparing another high-performance uranium nitride composite fuel, comprising:

[0018] Mix uranium nitride powder and metal reinforcement phase powder evenly to obtain uranium nitride / metal reinforcement phase mixed powder;

[0019] Under a protective atmosphere, subject the green body of uranium nitride / metal reinforcement phase composite fuel to field-assisted pressure rapid sintering to obtain a sintered body of uranium nitride / metal reinforcement phase composite fuel;

[0020] Subject the sintered body of uranium nitride / metal reinforcement phase composite fuel to surface micro-oxidation treatment to obtain a high-performance uranium nitride composite fuel.

[0021] The metal reinforcement phase powder of the present invention includes one or more of chromium, titanium, niobium, zirconium, tantalum, thorium, and uranium. The average particle size of the metal reinforcement phase powder is 5 nm to 200 μm; the average particle size of uranium nitride is 500 nm to 800 μm. 10 vol.% to 50 vol.% of metal reinforcement phase powder is added to the uranium nitride.

[0022] In the above steps, the steps of the surface micro-oxidation treatment include: under an air atmosphere or an argon-oxygen mixed gas atmosphere, subject the sintered body of uranium nitride / metal reinforcement phase composite fuel to surface micro-oxidation treatment at 50 to 150 °C for 2 to 24 h. Here, the density of the sintered body of uranium nitride / metal reinforcement phase composite fuel is 92% to 96%.

[0023] In the above steps, the steps of the field-assisted pressure rapid sintering include: under a protective atmosphere and pressure, keep the green body of uranium nitride / metal reinforcement phase composite fuel at a temperature of 600 to 1750 °C for 1 to 30 min; wherein, the protective atmosphere includes one or more of argon atmosphere, nitrogen atmosphere, argon atmosphere, and vacuum atmosphere, the pressure is 10 to 500 MPa, and the heating rate is 50 to 500 °C / min.

[0024] The present invention also provides a high-performance uranium nitride composite fuel, which is obtained by the above method for preparing a high-performance uranium nitride composite fuel. The thermal conductivity of the high-performance uranium nitride composite fuel at room temperature reaches 13.7 to 29.3 W·m -1 ·K -1 , and the coefficient of thermal expansion from room temperature to 100 °C is 7.6 to 10.5×10 -6 K -1 .

[0025] The beneficial effects of the present invention are:

[0026] 1. In the present invention, a metal reinforcing phase is added to uranium nitride, and then it is pressed, sintered in a high-temperature atmosphere or directly subjected to field-assisted pressure rapid sintering. Finally, the uranium nitride / metal reinforcing phase composite fuel green body is subjected to surface micro-oxidation treatment, so that a ternary uranium-nitrogen-oxygen compound and a metal oxide layer with excellent antioxidant performance can be formed on the surface of the green body, thereby improving the anti-water oxidation performance of the uranium nitride fuel.

[0027] 2. In the present invention, a metal reinforcing phase is added to uranium nitride, and then it is pressed, sintered in a high-temperature atmosphere or directly subjected to field-assisted pressure rapid sintering, and a uranium nitride / metal reinforcing phase composite fuel green body with a high density (above 92%) can be obtained, solving the problem of low density in the prior art.

[0028] 3. The present invention can reduce the sintering temperature of the fuel pellets (not exceeding 2100 °C), and realize low-cost batch sintering preparation at a relatively low temperature.

[0029] 4. In the present invention, by selecting a suitable metal reinforcing phase, such as chromium, titanium, niobium, zirconium, tantalum, thorium, uranium, and combining with the surface micro-oxidation technology, an oxide layer with excellent antioxidant performance can be formed on the surface of the fuel pellets, thereby improving the anti-water and oxygen performance of the uranium nitride / metal reinforcing phase composite fuel.

[0030] 5. The present invention preferably uses thorium in view of the scarcity of uranium resources and the abundance of thorium resources. Although thorium can be used as nuclear fuel, it cannot be used alone and must be used together with highly radioactive materials such as uranium. Therefore, adding thorium to uranium materials can not only prepare a thorium oxide protective layer through the micro-oxidation process to improve its antioxidant performance, but also realize the full utilization of thorium resources and save uranium resources.

[0031] 6. The present invention preferably uses uranium. The metallic uranium reinforcing phase can increase the uranium loading per unit volume in the composite fuel, thereby improving the fuel economy and reducing the nuclear power cost.

[0032] 7. The present invention adopts the direct micro-oxidation method, which has a simple process, low cost, and can effectively improve the anti-water and oxygen performance.

[0033] 8. The thermal expansion coefficients of the metal reinforcing phases such as chromium, titanium, niobium, zirconium, tantalum, thorium, and uranium added to uranium nitride in the present invention are lower than that of uranium nitride, and the thermal expansion coefficient of uranium nitride can be regulated. The thermal expansion coefficient from room temperature to 100 °C is 7.6 - 10.5×10 - 6 K -1 . The performance of the high-performance uranium nitride composite fuel of the present invention is excellent, and the thermal conductivity at room temperature reaches 13.7 - 29.3 W·m -1 ·K -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Process flow chart for the preparation of high-performance uranium nitride composite fuel

[0035] Figure 2 Morphology of the surface of the high-performance uranium nitride composite fuel in Example 4 after micro-oxidation treatment

[0036] Figure 3 Distribution state of metal elements on the surface of the high-performance uranium nitride composite fuel in Example 4 after micro-oxidation treatment

[0037] Figure 4 Distribution state of oxygen elements on the surface of the high-performance uranium nitride composite fuel in Example 4 after micro-oxidation treatment Detailed implementation manners

[0038] The technical solutions of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the scope of protection of the present invention.

[0039] The present invention provides a method for preparing a high-performance uranium nitride composite fuel, as Figure 1 shown, the preparation method includes:

[0040] S1. Mix uranium nitride powder and metal reinforcement phase powder evenly to obtain uranium nitride / metal reinforcement phase mixed powder.

[0041] Specifically, the average particle size of uranium nitride is 500 nm to 800 μm. For example, the average particle size of uranium nitride can be 100 nm, 1 μm, 200 μm, 400 μm, 600 μm.

[0042] Specifically, the average particle size of the metal reinforcement phase powder is 5 nm to 200 μm. For example, the average particle size of the metal reinforcement phase powder can be 10 nm, 500 nm, 1 μm, 50 μm, 100 μm, 150 μm.

[0043] The metal reinforcement phase powder of the present invention includes one or more of chromium (Cr), titanium (Ti), niobium (Nb), zirconium (Zr), tantalum (Ta), thorium (Th), and uranium (U). Here, the present invention can use one of Cr, Ti, Nb, Zr, Ta, Th, and U alone, or mix them for use.

[0044] Preferably, the present invention uses thorium (Th). Considering the scarcity of uranium resources and the abundance of thorium resources, although thorium can be used as nuclear fuel, it cannot be used alone and must be used together with highly radioactive materials such as uranium. Therefore, adding thorium to uranium materials can not only prepare a thorium oxide protective layer through a micro-oxidation process to improve its antioxidant performance, but also achieve the full utilization of thorium resources and save uranium resources.

[0045] Preferably, the present invention preferably uses uranium (U). The uranium metal reinforcement phase can increase the uranium loading per unit volume in the composite fuel, thereby improving fuel economy and reducing the cost of nuclear power.

[0046] The uranium nitride of the present invention is added with 10 vol.% to 50 vol.% (volume percentage concentration) of the metal reinforcement phase powder. For example, the uranium nitride can be added with 11 vol.%, 20 vol.%, 30 vol.%, 40 vol.% of the metal reinforcement phase powder.

[0047] The mixing method of the present invention can be ball milling. The mixing time can be 20 to 120 min.

[0048] S2. Press the uranium nitride / metal reinforcement phase mixed powder into a shape to obtain a green body of the uranium nitride / metal reinforcement phase composite fuel.

[0049] The pressing step of the present invention includes: loading the uranium nitride / metal reinforcement phase mixed powder into a cemented carbide mold for die pressing. Here, the die pressing can be carried out under a pressure of 100 to 500 MPa for 1 to 10 min. After die pressing, a green body of the uranium nitride / metal reinforcement phase composite fuel with a relative density of 45% to 60% is obtained.

[0050] S3. Under a protective atmosphere, subject the green body of the uranium nitride / metal reinforcement phase composite fuel to high-temperature atmosphere sintering to obtain a sintered body of the uranium nitride / metal reinforcement phase composite fuel.

[0051] The high-temperature atmosphere sintering step of the present invention includes: under a protective atmosphere, keeping the green body of the uranium nitride / metal reinforcement phase composite fuel at a temperature of 1000 to 2100 °C for 0.5 to 10 h to obtain a sintered body of the uranium nitride / metal reinforcement phase composite fuel with a relative density of 92% to 96%. For example, the temperature can be 1200 °C, 1400 °C, 1600 °C, 1800 °C, 2000 °C. The holding time can be 1 h, 3 h, 5 h, 7 h.

[0052] Among them, the protective atmosphere includes one or more of an argon atmosphere, a nitrogen atmosphere, an argon atmosphere, and a vacuum atmosphere.

[0053] Compared with the prior art, the sintering temperature usually exceeds 2100 °C. The present invention can reduce the sintering temperature of the fuel pellets (not exceeding 2100 °C) and achieve low-cost batch sintering preparation at a relatively low temperature.

[0054] Compared with the prior art, adding a second phase to uranium nitride fuel will reduce the uranium density in the composite fuel (lower than 90%), thereby reducing the fuel economy and seriously hindering the popularization and application of uranium nitride fuel in the commercial field. The present invention forms a composite fuel with high density through pressing and sintering in a high-temperature atmosphere, which can reach 92% - 96%.

[0055] S4. Perform surface micro-oxidation treatment on the uranium nitride / metal reinforcement phase composite fuel green body to obtain a high-performance uranium nitride composite fuel (also known as the finished product of uranium nitride / metal reinforcement phase composite fuel).

[0056] The steps of the surface micro-oxidation treatment of the present invention include: performing surface micro-oxidation treatment on the uranium nitride / metal reinforcement phase composite fuel green body at 50 - 150 °C for 2 - 24 h in an air atmosphere or an argon-oxygen mixed gas atmosphere. For example, the temperature can be 70 °C, 100 °C, 120 °C. The time for surface micro-oxidation treatment is 3 h, 3.5 h, 4 h.

[0057] Among them, in the argon-oxygen mixed gas atmosphere, the oxygen content is 2 vol.% - 10 vol.%. For example, the oxygen content is 4 vol.%, 6 vol.%, 8 vol.%.

[0058] The present invention adopts the direct micro-oxidation method to form a metal oxide layer with anti-oxidation and corrosion resistance and a uranium-nitrogen-oxygen ternary compound on the surface layer of the composite fuel pellet. This process is simple and has low cost, and can improve the anti-oxidation performance.

[0059] The present invention also provides a preparation method of a high-performance uranium nitride composite fuel, as Figure 1 shown, the preparation method includes:

[0060] A1. Mix uranium nitride powder and metal reinforcement phase powder evenly to obtain uranium nitride / metal reinforcement phase mixed powder.

[0061] Specifically, the average particle size of uranium nitride is 500 nm - 800 μm. For example, the average particle size of uranium nitride can be 100 nm, 1 μm, 200 μm, 400 μm, 600 μm.

[0062] Specifically, the average particle size of the metal reinforcement phase powder is 5 nm - 200 μm. For example, the average particle size of the metal reinforcement phase powder can be 10 nm, 500 nm, 1 μm, 50 μm, 100 μm, 150 μm.

[0063] The metal reinforcing phase powder of the present invention comprises one or more of chromium (Cr), titanium (Ti), niobium (Nb), zirconium (Zr), tantalum (Ta), thorium (Th), and uranium (U). Here, the present invention can use one of Cr, Ti, Nb, Zr, Ta, Th, and U alone, or can use them in combination.

[0064] 10 vol.% to 50 vol.% (volume percentage concentration) of the metal reinforcing phase powder is added to the uranium nitride of the present invention. For example, 11 vol.%, 20 vol.%, 30 vol.%, or 40 vol.% of the metal reinforcing phase powder can be added to the uranium nitride.

[0065] The mixing method of the present invention can be ball milling. The mixing time can be 20 to 120 min.

[0066] A2. Under a protective atmosphere, the green body of the uranium nitride / metal reinforcing phase composite fuel is subjected to field-assisted pressure rapid sintering to obtain a sintered body of the uranium nitride / metal reinforcing phase composite fuel.

[0067] The steps of the field-assisted pressure rapid sintering of the present invention include: under a protective atmosphere and pressure, keeping the green body of the uranium nitride / metal reinforcing phase composite fuel at a temperature of 600 to 1750 °C for 1 to 30 min; wherein, the protective atmosphere includes one or more of argon atmosphere, nitrogen atmosphere, argon atmosphere, and vacuum atmosphere, the pressure is 10 to 500 MPa, and the heating rate is 50 to 500 °C / min. For example, the temperature is 800 °C, 1000 °C, 1200 °C, or 1400 °C. The holding time is 2 min, 20 min, or 25 min. The pressure is 20 MPa, 100 MPa, 200 MPa, or 300 MPa. The heating rate is 100 °C / min, 200 °C / min, or 300 °C / min.

[0068] The field-assisted pressure rapid sintering of the present invention can obtain a sintered body of the uranium nitride / metal reinforcing phase composite fuel with a relative density of 92% to 96%. Moreover, the present invention can reduce the sintering temperature of the fuel pellets to 600 to 1800 °C, and shorten the time to 1 to 30 min.

[0069] Compared with the prior art which usually uses pressure sintering techniques such as hot pressing sintering and spark plasma sintering to suppress the decomposition behavior of uranium nitride at high temperatures, the present invention obtains uranium nitride fuel pellets with a relatively high density by adding a metal reinforcing phase. And in the prior art, only one uranium nitride fuel pellet can be sintered at a time by the above methods, which cannot meet the requirements of batch preparation of fuel pellets and is not conducive to the commercial application of uranium nitride fuel. The high-temperature atmosphere sintering in step S3 and the field-assisted pressure rapid sintering in step A2 of the present invention can obtain high-density high-performance uranium nitride composite fuel, and can sinter high-performance uranium nitride composite fuel in batches.

[0070] A3. Subject the uranium nitride / metal reinforcement phase composite fuel green body to surface micro-oxidation treatment to obtain a high-performance uranium nitride composite fuel (also known as the finished uranium nitride / metal reinforcement phase composite fuel).

[0071] The steps of the surface micro-oxidation treatment of the present invention include: subjecting the uranium nitride / metal reinforcement phase composite fuel green body to surface micro-oxidation treatment at 50 - 150°C for 2 - 24 h in an air atmosphere or an argon-oxygen mixed gas atmosphere. For example, the temperature can be 70°C, 100°C, 120°C. The time of the surface micro-oxidation treatment is 3 h, 3.5 h, 4 h.

[0072] Among them, in the argon-oxygen mixed gas atmosphere, the oxygen content is 2 vol.% - 10 vol.%. For example, the oxygen content is 4 vol.%, 6 vol.%, 8 vol.%.

[0073] The present invention adopts the direct micro-oxidation method to form a metal oxide layer with anti-oxidation and corrosion resistance and a uranium-nitrogen-oxygen ternary compound on the surface layer of the composite fuel pellet. This process is simple and low-cost, and can improve the anti-oxidation performance.

[0074] In summary, in the present invention, a metal reinforcement phase is added to uranium nitride, and then it is pressed, sintered in a high-temperature atmosphere or directly subjected to field-assisted pressure rapid sintering, and a uranium nitride / metal reinforcement phase composite fuel green body with a high density (above 92%) can be obtained. Then, subject the uranium nitride / metal reinforcement phase composite fuel green body to surface micro-oxidation treatment, an oxide layer with excellent anti-oxidation performance can be formed on the surface of the green body, and at the same time, a small amount of oxygen is dissolved in the surface layer of uranium nitride, obtaining a uranium-nitrogen-oxygen ternary compound with good stability, mechanical strength, melting point, thermal conductivity and corrosion resistance, and improving the anti-water oxidation performance of uranium nitride fuel.

[0075] The present invention also provides a high-performance uranium nitride composite fuel, which is obtained by the preparation method of the above-mentioned high-performance uranium nitride composite fuel. The thermal conductivity of the high-performance uranium nitride composite fuel at room temperature reaches 13.7 - 29.3 W·m -1 ·K -1 , and the thermal expansion coefficient from room temperature to 100°C is 7.6 - 10.5×10 -6 K -1 .

[0076] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well-known to those skilled in the art.

[0077] The present invention is described in detail below through examples and experimental examples. However, these are only examples and do not limit the present invention in any form.

[0078] Example 1

[0079] Add 20 vol.% of metal Cr powder with an average particle size of 60 nm to uranium nitride powder with an average particle size of 200 μm. After mixing the two evenly, a mixture powder of uranium nitride and metal reinforcement phase Cr is obtained. Then, load the mixture powder into a mold and use the field-assisted pressure rapid sintering (also known as electric field-assisted sintering such as spark plasma sintering) method in an argon atmosphere and at 80 MPa, with a heating rate of 50 °C / min, hold for 5 min at a temperature of 1700 °C for pressure rapid sintering to obtain a metal Cr-reinforced uranium nitride composite fuel pellet with a relative density of 96%. Subject the prepared composite fuel pellet to surface micro-oxidation treatment at 50 °C for 24 h in an argon-oxygen mixed gas atmosphere with an oxygen content of 5 vol.%, to form a metal Cr oxide layer and a uranium-nitrogen-oxygen ternary compound on the surface layer of the composite fuel pellet. The thermal conductivity of this high-performance uranium nitride composite fuel reaches 25.8 W·m -1 ·K -1 , and the thermal expansion coefficient from room temperature to 100 °C is 7.8×10 -6 K -1 。

[0080] Example 2

[0081] Add 10 vol.% of metal Ti powder with an average particle size of 60 nm to uranium nitride powder with an average particle size of 800 nm. After mixing the two evenly, a mixture powder of uranium nitride and metal Ti reinforcement phase is obtained. Then, press the mixture powder into a green body with a relative density of 60%, and then carry out high-temperature atmosphere sintering at a temperature of 1500 °C for 0.5 h in a nitrogen atmosphere to obtain a metal Ti-reinforced uranium nitride composite fuel pellet with a relative density of 92%. Subject the prepared composite fuel pellet to surface micro-oxidation treatment at 80 °C for 3 h in an air atmosphere, to form a metal Ti oxide layer and a uranium-nitrogen-oxygen ternary compound on the surface layer of the composite fuel pellet. The thermal conductivity of this high-performance uranium nitride composite fuel reaches 13.7 W·m -1 ·K -1 , and the thermal expansion coefficient from room temperature to 100 °C is 8.9×10 -6 K -1 。

[0082] Example 3

[0083] Add 15 vol.% of metal Nb powder with an average particle size of 20 nm to uranium nitride powder with an average particle size of 500 nm. After mixing the two evenly, a mixture powder of uranium nitride and metal Nb reinforcement phase is obtained. Then, the mixture powder is pressed into a green compact with a relative density of 55%. Subsequently, high-temperature atmosphere sintering is carried out at 2100 °C for 6 h in an argon-5 vol.% nitrogen mixed atmosphere to obtain a metal Nb-reinforced uranium nitride composite fuel pellet with a relative density of 94%. The prepared composite fuel pellet is subjected to surface micro-oxidation treatment at 50 °C for 5 h in an argon-oxygen mixed gas atmosphere with an oxygen content of 10 vol.%, and a metal Nb oxide layer and a uranium-nitrogen-oxygen ternary compound are formed on the surface layer of the composite fuel pellet. The thermal conductivity of this high-performance uranium nitride composite fuel reaches 19.2 W·m -1 ·K -1 , and the thermal expansion coefficient from room temperature to 100 °C is 8.6×10 -6 K -1 .

[0084] Example 4

[0085] Add 20 vol.% of metal Zr powder with an average particle size of 100 nm to uranium nitride powder with an average particle size of 10 μm. After mixing the two evenly, a mixture powder of uranium nitride and metal Zr reinforcement phase is obtained. Then, the mixture powder is pressed into a green compact with a relative density of 45%. Subsequently, high-temperature atmosphere sintering is carried out at 1700 °C for 10 h in an argon atmosphere to obtain a metal Zr-reinforced uranium nitride composite fuel pellet with a relative density of 95%. The prepared composite fuel pellet is subjected to surface micro-oxidation treatment at 150 °C for 4 h in an argon-oxygen mixed gas atmosphere with an oxygen content of 4 vol.%, and a metal Zr oxide layer and a uranium-nitrogen-oxygen ternary compound are formed on the surface layer of the composite fuel pellet. The thermal conductivity of this high-performance uranium nitride composite fuel reaches 15.8 W·m -1 ·K -1 , and the thermal expansion coefficient from room temperature to 100 °C is 8.1×10 -6 K -1 .

[0086] As Figure 2 shown, the morphology of the high-performance uranium nitride composite fuel after surface micro-oxidation treatment. Specifically, the composite pellet consists of a light gray uranium nitride matrix and a dark gray metal reinforcement phase. The metal reinforcement phase added to the uranium nitride has a high relative density and a clear interface with the uranium nitride matrix, indicating that there is no obvious diffusion or reaction behavior between the two, and they have good chemical compatibility.

[0087] As Figure 3As shown, the distribution state of metal elements on the surface of high-performance uranium nitride composite fuel after micro-oxidation treatment. Specifically, after the surface micro-oxidation treatment, the interface between the metal reinforcement phase and the uranium nitride matrix is clear, indicating that there is no obvious diffusion or reaction behavior between the two during the surface micro-oxidation treatment, and they have good chemical compatibility.

[0088] As Figure 4 shown, the distribution state of oxygen elements on the surface of high-performance uranium nitride composite fuel after micro-oxidation treatment. Specifically, after the micro-oxidation treatment, oxygen elements are mainly distributed in the metal reinforcement phase, and trace amounts of oxygen are distributed in the uranium nitride matrix. It shows that during the oxidation treatment process, due to the stronger affinity between metal and oxygen, oxygen preferentially reacts with the surface metal to form a dense and uniform oxide layer. At the same time, trace amounts of oxygen also diffuse into the uranium nitride to form uranium-nitrogen-oxygen ternary compounds.

[0089] Example 5

[0090] Add 50 vol.% of metal reinforcement phase powder Th with an average particle size of 200 μm to uranium nitride powder with an average particle size of 500 μm. After mixing the two evenly, a mixture powder of uranium nitride and metal Th reinforcement phase is obtained. Then, the mixture powder is loaded into a mold and sintered rapidly under pressure by using a field-assisted sintering method such as spark plasma sintering in a nitrogen atmosphere at 10 MPa, with a heating rate of 500 °C / min, and held at 1550 °C for 1 min for pressure-assisted rapid sintering to obtain a metal Th-reinforced uranium nitride composite fuel pellet with a relative density of 92%. The prepared composite fuel pellet is subjected to surface micro-oxidation treatment at 75 °C for 5 h in an argon-oxygen mixed gas atmosphere with an oxygen content of 3 vol.%, forming a metal Th oxide layer and uranium-nitrogen-oxygen ternary compounds on the surface layer of the composite fuel pellet. The thermal conductivity of this high-performance uranium nitride composite fuel reaches 29.3 W·m -1 ·K -1 , and the thermal expansion coefficient from room temperature to 100 °C is 9.6×10 -6 K -1 .

[0091] Example 6

[0092] Add 30 vol.% of metallic U powder with an average particle size of 100 μm to uranium nitride powder with an average particle size of 800 μm. After mixing the two evenly, a mixture powder of uranium nitride and metallic U reinforcement phase is obtained. Then, press the mixture powder into a green body of the mixture with a relative density of 50%. Subsequently, conduct high-temperature atmosphere sintering at 1000 °C for 2 h in an argon atmosphere to obtain a metallic U-reinforced uranium nitride composite fuel pellet with a relative density of 96%. Subject the prepared composite fuel pellet to surface micro-oxidation treatment at 70 °C for 2 h in an argon-oxygen mixed gas atmosphere with an oxygen content of 2 vol.%, forming a metallic U oxide layer and a ternary uranium nitride-oxide compound on the surface layer of the composite fuel pellet. The thermal conductivity of this high-performance uranium nitride composite fuel reaches 18.0 W·m -1 ·K -1 , and the coefficient of thermal expansion from room temperature to 100 °C is 10.5×10 -6 K -1 .

[0093] Example 7

[0094] Add 20 vol.% of metallic U powder with an average particle size of 200 μm to uranium nitride powder with an average particle size of 350 μm. After mixing the two evenly, a mixture powder of uranium nitride and metallic U reinforcement phase is obtained. Then, load the mixture powder into a mold and use a method of rapid sintering assisted by an equal-field electric field such as spark plasma sintering under a vacuum atmosphere and 500 MPa, with a heating rate of 100 °C / min, and hold at 600 °C for 30 min for rapid pressure sintering to obtain a metallic U-reinforced uranium nitride composite fuel pellet with a relative density of 95%. Subject the prepared composite fuel pellet to surface micro-oxidation treatment at 70 °C for 2 h in an argon-oxygen mixed gas atmosphere with an oxygen content of 2 vol.%, forming a metallic U oxide layer and a ternary uranium nitride-oxide compound on the surface layer of the composite fuel pellet. The thermal conductivity of this high-performance uranium nitride composite fuel reaches 16.9 W·m -1 ·K -1 , and the coefficient of thermal expansion from room temperature to 100 °C is 9.9×10 -6 K -1 .

[0095] Example 8

[0096] 15 vol.% of metallic Ta powder with an average particle size of 5 nm was added to uranium nitride powder with an average particle size of 600 μm. After the two were mixed evenly, a mixture powder of uranium nitride and metallic Ta reinforcement phase was obtained. Then, the mixture powder was loaded into a mold and subjected to pressure-assisted rapid sintering at 80 MPa in a vacuum atmosphere using a spark plasma sintering or other electric field-assisted sintering method at a heating rate of 200 °C / min and held at 1750 °C for 20 min to obtain a metallic Ta-reinforced uranium nitride composite fuel pellet with a relative density of 94%. The prepared composite fuel pellet was subjected to surface micro-oxidation treatment at 60 °C for 4 h in an argon-oxygen mixed gas atmosphere with an oxygen content of 2 vol.%, forming a metallic Ta oxide layer and a uranium-nitrogen-oxygen ternary compound on the surface layer of the composite fuel pellet. The thermal conductivity of the high-performance uranium nitride composite fuel at room temperature reached 20.3 W·m -1 ·K -1 , and the coefficient of thermal expansion from room temperature to 100 °C was 7.6×10 -6 K -1 .

[0097] In summary, the thermal conductivity of the high-performance uranium nitride composite fuel of the present invention reaches 25.8 W·m -1 ·K -1 , and the coefficient of thermal expansion from room temperature to 100 °C is 7.8×10 -6 K -1 , and a high-performance uranium nitride composite fuel with a high relative density (above 90%) is formed.

[0098] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made in these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-performance uranium nitride composite fuel, characterized in that: include: The uranium nitride powder and the metal reinforcement phase powder are uniformly mixed to obtain a uranium nitride / metal reinforcement phase mixed powder; Pressing the uranium nitride / metal-enhanced phase mixed powder into a shape to obtain a uranium nitride / metal-enhanced phase composite fuel green body; Under a protective atmosphere, the uranium nitride / metal enhanced phase composite fuel green body is subjected to high temperature atmosphere sintering to obtain a uranium nitride / metal enhanced phase composite fuel green body; The surface of the uranium nitride / metal enhanced phase composite fuel billet is subjected to micro-oxidation treatment to obtain a high performance uranium nitride composite fuel.

2. A method for preparing a high-performance uranium nitride composite fuel, characterized in that: include: The uranium nitride powder and the metal reinforcement phase powder are uniformly mixed to obtain a uranium nitride / metal reinforcement phase mixed powder; Under a protective atmosphere, the uranium nitride / metal enhanced phase composite fuel green body is subjected to field assisted pressure rapid sintering to obtain a uranium nitride / metal enhanced phase composite fuel green body; The surface of the uranium nitride / metal enhanced phase composite fuel billet is subjected to micro-oxidation treatment to obtain a high performance uranium nitride composite fuel.

3. The preparation method according to claim 1 or 2, characterized in that: The metal reinforcement phase powder includes one or more of chromium, titanium, niobium, zirconium, tantalum, thorium and uranium.

4. The preparation method according to claim 1 or 2, characterized in that: The average particle size of the metal reinforcement phase powder is 5nm to 200μm; The average particle size of the uranium nitride is 500nm-800μm.

5. The preparation method according to claim 1 or 2, characterized in that: 10 vol.% to 50 vol.% of metal reinforcement phase powder is added to the uranium nitride.

6. The preparation method according to claim 1 or 2, characterized in that: The step of surface micro-oxidation treatment comprises: In an air atmosphere or an argon-oxygen mixed gas atmosphere, the uranium nitride / metal enhanced phase composite fuel agglomerate is subjected to a surface micro-oxidation treatment at 50-150° C. for 2-24 hours.

7. The preparation method according to claim 1, characterized in that: The step of high temperature atmosphere sintering comprises: Under a protective atmosphere, the uranium nitride / metal enhanced phase composite fuel green body is kept at a temperature of 1000-2100° C. for 0.5-10 hours; wherein the protective atmosphere includes one or more of argon atmosphere, nitrogen atmosphere, argon atmosphere, and vacuum atmosphere.

8. The preparation method according to claim 7, characterized in that: The density of the uranium nitride / metal enhanced phase composite fuel green body is 45% to 60%; The density of the uranium nitride / metal enhanced phase composite fuel agglomerate is 92% to 96%.

9. The preparation method according to claim 2, characterized in that: The field-assisted pressure rapid sintering step comprises: Under a protective atmosphere and pressure, the uranium nitride / metal enhanced phase composite fuel green body is kept at a temperature of 600-1750° C. for 1-30 min; wherein the protective atmosphere includes one or more of an argon atmosphere, a nitrogen atmosphere, an argon atmosphere, and a vacuum atmosphere, the pressure is 10-500 MPa, and the heating rate is 50-500° C. / min.

10. A high performance uranium nitride composite fuel, characterized in that: The high-performance uranium nitride composite fuel is obtained by the preparation method of the high-performance uranium nitride composite fuel according to any one of claims 1 to 9, and the thermal conductivity of the high-performance uranium nitride composite fuel at room temperature reaches 13.7 to 29.3 W·m -1 ·K -1 The thermal expansion coefficient from room temperature to 100°C is 7.6 to 10.5×10 -6 K -1 .

Citation Information

Patent Citations

  • Dispersion fuel pellet for nuclear power station and preparation method of dispersion fuel pellet

    CN117854755A